Metamizole for Postoperative Pain Therapy in Infants Younger than 1 Year - Sümpelmann, Robert; Fieler, Melanie; Eich, Christoph; Becke, Karin; Badelt, Gregor; Leimkühler, Klaus; Dennhardt, Nils (European Journal of Pediatric Surgery, 2017)
Background Due to possible serious adverse drug reactions (ADRs), the use of metamizole for postoperative pain therapy in infants is a subject of debate. Safety studies with large sample sizes are missing.Aim This prospective multicenter observational study was conducted to evaluate the use of metamizole in infants younger than 1 year undergoing surgery with a particular focus on possible serious ADRs (e.g., hemodynamic, anaphylactic or respiratory reactions, and agranulocytosis).Methods Infants aged up to 1 year (American Society of Anesthesiologists [ASA] I–III) receiving a single dose of metamizole for postoperative pain therapy were enrolled. Patient demographics, main and secondary diagnosis, surgical procedures performed, metamizole dose, hemodynamic data, use of other analgesics and regional blocks, results of pain measurement, and incidence of ADRs were documented using a standardized case report form.Results A total of 316 infants observed at five pediatric centers were included for analysis (age 4.4 ± 3.7 [0.06–12] months). Mean metamizole dose was 17.8 ± 3.1 (9.2–29.8) mg·kg−1. Mean arterial pressure (MAP) remained stable during metamizole infusion (MAP before infusion 45 ± 9.5 [25–95] and after infusion 45 ± 9.2 [25–99] mm Hg). Erythema was observed in one patient (ADRs total: 0.3%, 95% confidence interval: 0.27–0.32). No respiratory adverse events directly related to the metamizole administration and no clinical signs of agranulocytosis were reported.Conclusion Single intravenous doses of metamizole used for prevention or treatment of postoperative pain were safe in more than 300 infants younger than 1 year. The statistical probability of serious ADRs (e.g., hemodynamic, anaphylactic or respiratory reactions) was lower than 1%. The sample size and follow-up were not sufficient to detect agranulocytosis.
Keywords: metamizole; dipyrone; infants; postoperative pain therapy; adverse drug reactions